Activity of Children’s Hospices for Family on the Basis of Analysis of Internet Resources Available on Hospice Websites - Godawa, Grzegorz (Zakład Historii Edukacji Instytutu Pedagogiki Uniwersytetu Wrocławskiego, 2018)
An ill child’s family may use support offered by various institutions and social organisations. One of the forms of boosting an ill child’s family is support offered by children’s hospices. Their aim is to ensure the optimal quality of the child’s life and help other family members. Hospice websites are an important source of information for parents who would like to receive support. The aim of the research was to present what kind of support is offered to ill children and their families. The research was conducted with the use of qualitative analysis of data available on websites of 31 children’s hospices in Poland. The analysis of websites showed that support offered by the institutions meets palliative care standards. This kind of support satisfies ill children’s needs, improves the quality of their life and boosts other family members. The way of presenting information is specific to each website, which emphasises the variety of approaches. It sometimes raises questions about the determinants of social support. Resources vailable on hospice websites meet the need to receive simple and useful information which helps parents make important decisions.
Keywords: ill child; hospice; family; support; Internet resources